Frequency of Ventricular Septal Defect in Down Syndrome Patients Presenting at a Tertiary Care Hospital - Dar, Rehab Anjum; Javed, Ahsan; Batool, Iffat; Raza, Ali; Israr, Muhammad Uzair; Sadiq, Rizwan (Annals of Punjab Medical College, 2023)
Background: In Down syndrome, ventricular septal defect (VSD) is a typical cardiac abnormality. Objective: The estimation of the frequency of diabetes mellitus in Hepatitis C patients is the main objective of this study. Study Design: Cross sectional study. Settings: The research was done in the Department of Cardiology Shaikh Zayed Hospital, Lahore Pakistan. Duration: March 2022 to August 2022. Methods: Total sample of participants would be determined by using Raosoftware. The sample size was selected to be n=100 after taking prevalence of 58.3%, 9% margin of error and confidence level at 95 %. The statistical analysis was done by using SPSS version 20. Results: The average age of the 100 enrolled individuals who tested positive for hepatitis C RNA was 48.46 9.05 years. With a female to male ratio of 1.9:1, the sample included 66 women and 34 men. There were 55 (55%) people with diabetes out of 100, however 29 (29%) were found accidentally during routine laboratory testing; the other people were either on dietary restrictions or weren’t taking their prescriptions as prescribed. The majority of the patients (n=24, or 24%) had HBA1C >7.6 i.e., while another 23 (or 23%) had HBA1C between 6.5-7.0%, and the other 8 (or 8%) had HBA1C between 7.1-7.5%. Conclusion: Due to the increasing incidence of diabetes in HCV RNA-positive patients, studies are necessary to develop viable and inexpensive techniques for the monitoring and treatment of diabetes in hepatitis C patients. These strategies must be suitable for use in hepatitis C patients.